1995
DOI: 10.1113/jphysiol.1995.sp020865
|View full text |Cite
|
Sign up to set email alerts
|

Decreased calcium currents in motor nerve terminals of mice with Lambert‐Eaton myasthenic syndrome.

Abstract: The effects of immunoglobulin G (IgG4. Ca2P currents in controls were unaffected by addition of nifedipine but were reduced by 37 % upon addition of w-conotoxin GVIA. In LEMS animals, however, the currents were depressed by 43 % by nifedipine but were unaffected by w-conotoxin GVIA. Thus, LEMS is associated with reduced Ca2+ currents and a shift to dihydropyridine sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…In conclusion, LES antibodies nearly eliminated the non-L HVA current in murine motoneurons while sparing significant L-type current. This conclusion is in agreement with a recent report that a large fraction of the extracellularly recorded calcium current in mouse motor nerve terminals exposed to LES antibodies is blocked by dihydropyridines (Smith et al, 1995). LES sera seem to have a much more profound effect on calcium currents in motoneurons than in other native tissues examined (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In conclusion, LES antibodies nearly eliminated the non-L HVA current in murine motoneurons while sparing significant L-type current. This conclusion is in agreement with a recent report that a large fraction of the extracellularly recorded calcium current in mouse motor nerve terminals exposed to LES antibodies is blocked by dihydropyridines (Smith et al, 1995). LES sera seem to have a much more profound effect on calcium currents in motoneurons than in other native tissues examined (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Subsequently, numerous studies have established a LES serum-induced decrease in calcium influx in a variety of cells (see introductory remarks). Recently it has been demonstrated that LES antibodies decrease mixed sodium and calcium currents at mouse nerve terminals (Smith et al, 1995). Here, we provide the first study directly quantifying the effects of LES sera on isolated calcium currents in motoneurons.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Up-regulation of L-type channels is a well reported form of plasticity at murine neuromuscular junction. It occurs in adult mice treated chronically with Lambert-Eaton myasthenic syndrome plasma (Smith et al, 1995;Xu et al, 1998;Flink and Atchison, 2002), reinnervating motor endplates following acute nerve damage (Katz et al, 1996) or botulinum toxin-poisoned nerve terminals (Santafe et al, 2000). L-type channels are also involved in ACh release in neonatal rats (Sugiura and Ko, 1997).…”
Section: N-and R-type Ca 2؉ Channels At Nmj In Tottering Micementioning
confidence: 99%
“…The release of acetylcholine at the patient's NMJ may have been decreased even in the remission state (Figure 2c). In mice injected with serum from LEMS patients, Ca 2+ currents were significantly depressed by nifedipine, a L-type VGCC blocker, but were unaffected by GviA, an ω peptide antagonist of N-type VGCC, 11) suggesting that L-type VGCC plays an important role in neurotransmission in LEMS. Therefore, it is reasonable to postulate that L-type VGCC blockers such as diltiazem might block the remaining component of neurotransmitter release, thus worsening the muscle weakness (Figure 2d).…”
Section: Vol 44 Nomentioning
confidence: 98%